Polusi Transportasi : Dampak Serta Besarnya Kemauan Pencemar Membayar Kompensasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The emission of pollutants by vehicles has impacts and contributes greatly to the health of the people. Every time, the need for motor vehicles increases. This condition will be followed by the increase ini pollution level in the atmosphere. This social imbalance must be solved applying polluter pay principles. The data for this research was collected by using questionnaire to know the willingness to pay. It was found that the willingness to pay in this research was Rp. 87,14 per liter gasoline used.